PROSES PEMBUATAN MESIN PENGEPRES SERBUK KAYU UNTUK MEDIA PEMBIBITAN JAMUR - Dhani Aryanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
Oyster mushroom cultivation business is very tempting. From a financial point of view, it can be said that this business is feasible to run. Especially for hobbyists or entrepreneurs, this business is quite fun and interesting. If we observe, the interest in this cultivation business continues to increase from year to year. Of course, there are many factors that are the reason for the increasing interest in this business, ranging from just a hobby, the mushroom factor as a healthy food or mushrooms as a future food. That means this business will continue to grow for a long time.From the above, it can be concluded that the development of a business cannot be separated from the existence of appropriate technology. So it takes a pressing machine to compact the planting media in the form of a mixture of sawdust. In a site survey to a place for making consumption mushroom growing media. The pressing process is still manual, but there is also a machine. Pressing with the machine is still at risk of pinching the hand so that it can slow down the production process. Therefore, the risk of making this pressing machine is minimized and the automatic production process can run smoothly so that more results are obtained. The machine works up and down by using the clutch lever, pressing the sawdust with a specified density level, namely the initial height of 230 mm to 190 mm. Keywords: Pressing Machine, Mushroom